Revenue requirements for mobile operators with ultra-high mobile broadband data traffic growth. - Jan Werding (International Telecommunications Society (ITS), 2010)
Mobile broadband data access over cellular networks has been established as a major new service in just a few years. The mobile broadband penetration has risen from almost zero to between 10 and 15 per cent in Western European leading markets from 2007 to the end of 2009. More than 75% of network traffic was broadband data in 2009, and the data volumes are growing rapidly. But the revenue generation is the reverse as the average for operators in Europe in 2009 was around 77 per cent of service revenues from voice, 10 per cent from SMS and 13 per cent from other data. Voice and broadband data service are built on two quite different business models. Voice pricing is volume based. Revenue depends linearly on the number of voice minutes. Broadband data service on the other hand is mainly flat fee based even if different levels are being introduced as well as tiers. Revenue is decoupled from traffic and therefore also from operating costs and investment requirements. This is what we define as a revenue gap. Earnings as well as internal financing will suffer from increasing traffic per user unless the flat fee can be raised or changed to volume based, other revenue can be obtained and/or operating costs and investments can be reduced accordingly. Observable trends and common forecasts indicate strong growth of mobile broadband traffic as well as declining revenue from mobile voice in the next five year period. This outlook suggests a prospective revenue gap with weak top-line growth and expanding operating costs and investment requirements. This is not only a profitability and cash flow issue. It may also severely restrict the industry's revenue and profit growth potential if it is handled mainly by cost-cutting. In sections 2 - 4 we describe related work, our contribution, the specific research questions as well as the methodology and its problems. Section 5 is an overview of mobile operators' revenue, its sources and development till today. Section 6 presents trends, developments and published forecasts that may be relevant for the future. Section 7 contains our conclusions.
Keywords: L96; 330; Mobile broadband; mobile operator revenues; revenue requirements; voice revenues; non-voice revenues